Biology of the immature stages of Strymon crambusa (Lycaenidae, Theclinae) on Oxalidaceae - Neuza Aparecida Pereira da Silva; Cintia Lepesqueur; Agnelo Rodrigues Souza; Helena Castanheira Morais (Revista Brasileira de Entomologia, 2016)
ABSTRACT We document the biology and morphology of the egg, caterpillar, and pupa of Strymon crambusa (Hewitson, 1874), a Neotropical Eumaeini. In the Cerrado, the caterpillar feeds on the inflorescences and leaves of Oxalis L. S. crambusa has four larval instars, all of which are illustrated. The density of caterpillars on plants is higher than that recorded for leaf-feeding caterpillars and other flower-feeding Eumaeini, which suggests that the species is a specialist on Oxalidaceae in the Cerrado.